2013
DOI: 10.1016/j.still.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural management on chemical and biochemical properties of a semiarid soil from central Spain

Abstract: Effects of agricultural management on chemical and biochemical properties of a semiarid soil from central Spain. Soil Tillage Research 134, 49-55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…In the same way, the soil N content showed a strong negative correlation (r 2 =-0.759; p< 0.0005) to the δ 15 N signature in the terraced soil layers (1A, 2A and 3A) pointing to an open N cycle with sustained N losses in the cultivated soil. Accordingly, the results of other investigations reported a high positive correlation between the 15 N abundance and N losses (HÖGBERG & JOHANNISSON 1993;GONZÁLEZ-PRIETO et al 2013).…”
Section: R2mentioning
confidence: 72%
See 1 more Smart Citation
“…In the same way, the soil N content showed a strong negative correlation (r 2 =-0.759; p< 0.0005) to the δ 15 N signature in the terraced soil layers (1A, 2A and 3A) pointing to an open N cycle with sustained N losses in the cultivated soil. Accordingly, the results of other investigations reported a high positive correlation between the 15 N abundance and N losses (HÖGBERG & JOHANNISSON 1993;GONZÁLEZ-PRIETO et al 2013).…”
Section: R2mentioning
confidence: 72%
“…Koerner et al (1999) reported that the mean δ 15 N of soil increased with the intensity of former land use and that the δ 15 N of understory plant and soil appear to be excellent tracers of previous land use in forests, and could be used in historical studies. González-Prieto et al (2013) also found that δ 15 N is a potential tracer of changing land use because it allows discriminating among soils with similar carbon and nitrogen stocks but under differing land use. A dual isotope approach with carbon (δ 13 C) and nitrogen (δ 15 N) is particularly useful in studying SOM sources (PETERSON & FRY 1987).…”
Section: Introductionmentioning
confidence: 95%
“…It is therefore possible that following CT, part of the original SOM and the added crop residues could be below 14 cm which is the lower sampling depth under RT. Previous studies have shown an increased SOM only in the surface layer (0-10 cm) without a change in deeper layers under different conservation tillage systems in semi-arid agroecosystems (Alvaro-Fuentes et al, 2009;Melero et al, 2011;González-Prieto et al, 2013). The increased SOM content in the topsoil is frequently counteracted with a decline at lower soil depths (Omidi et al, 2008;Geisseler and Horwath, 2009;Mijangos and Garbisu, 2010), probably diluting the SOM through the surface soil profile.…”
Section: Resultsmentioning
confidence: 94%
“…However, the PT+2RT treatment had a weaker ability to reduce subsoil compaction and could not maintain soil nutrient homogeneous distribution, which suggests that PT should be applied every other year in rotation with shallow tillage in the winter wheat-summer maize system in northern China. González-Prieto et al [ 31 ] studied the effect of different tillage practices on soil properties in a calcic haploxeralf in a leguminous-cereal rotation system and found that the extent and duration of effects on soil properties under PT treatment could be maintained for 2 years; otherwise, the cone index and BD sharply increased. However, Pierce et al [ 8 ] analysed data from long-term field experiments on a Capac loam in a corn-rye system and found that the improvement of most soil physical quality parameters and the stratification ratio of soil nutrients under rotational tillage practice returned to initial levels after approximately 4 or 5 years of PT.…”
Section: Discussionmentioning
confidence: 99%